(untitled) (Edad Media. Revista de Historia, 2023)
The aim of this article is to analyse the relations between women and the commercial sector in the Late Middle Ages in the city of Seville. To this end, a collection of historical documentation from the Notarial Protocols have been selected: debts, payment agreements, ship charterings or constitutions of commercial companies. The circumstances and results of their activity in a host of commercial sectors have been described. The wide variety of commercial relations and products implicated in their business has been of especial attention, as well as the role the civil status played in that matter, focusing on the restrictive or profitable part of matrimony. Finally, this article provides evidence of the presence of women in a public space of the city, such as the market.